2017
DOI: 10.6016/zdravvestn.2463
|View full text |Cite
|
Sign up to set email alerts
|

The impact of open access on the medical literature: a review of current literature

Abstract: IzvlečekIzhodišča: Namen članka je podati pregled vpliva odprtega dostopa na znanstvene objave v medicini glede na tri kategorije: citiranost, vidnost in omembe v socialnih medijih.Metode: Podatke smo pridobili z iskalno strategijo, ki je vsebovala ključne besede, kot so "open access", "citation impact", "citation advantage", "citations count", "article download", "article usage", "social media attention" in "altmetrics".Rezultati: Z iskalno strategijo, ki smo jo uporabili v treh zbirkah podatkov, smo pridobil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
(123 reference statements)
0
2
0
Order By: Relevance
“…Regarding OACA, they looked at nine studies across many disciplines and found variation of methods and materials, but ultimately the citation advantage ranged from -5% to 83% [ 18 ]. Turk [ 19 ] published an overview on OA, pertaining only to medical articles, looking at OA factors in which studies of possible OACA mostly found a citation advantage, but articles reporting randomized controlled trial (RCT) results revealed no OACA. Turk [ 19 ] indicated that other factors may influence a citation advantage for OA such as discipline, impact factor of journals studied, and the early view effect and selection bias Craig noted in 2007 [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding OACA, they looked at nine studies across many disciplines and found variation of methods and materials, but ultimately the citation advantage ranged from -5% to 83% [ 18 ]. Turk [ 19 ] published an overview on OA, pertaining only to medical articles, looking at OA factors in which studies of possible OACA mostly found a citation advantage, but articles reporting randomized controlled trial (RCT) results revealed no OACA. Turk [ 19 ] indicated that other factors may influence a citation advantage for OA such as discipline, impact factor of journals studied, and the early view effect and selection bias Craig noted in 2007 [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, the effect of OA on the visibility or impact of scientific publications has become one of the most important issues in the fields of bibliometrics and information science. There has been much discussion and analysis as to whether OA affects the number of times a publication is cited (Turk, 2016). A large number of studies have been carried out on the effect of OA on citation rates to articles.…”
Section: Introductionmentioning
confidence: 99%